Crime and conspicuous consumption (2010)
This paper develops an incomplete information model wherein individuals face a trade-off between status and security when deciding the optimal amount of conspicuous consumption. On the one hand, we assume that individuals derive utility from status, which is obtained by signaling wealth through the consumption of an observable good. On the other hand, the increased consumption of observable goods also signals wealth to a criminal audience, thus increasing the chance of becoming target for criminal activities. The paper proposes an information channel through which crime distorts consumption decisions; this channel is different in nature from the channel where by crime acts as a direct tax on observable and stealable consumption goods. More precisely, we argue that, in the presence of crime, individuals reduce their consumption of observable goods, not only because criminals may steal these goods, but also because it reveals information that could be used by criminals to target individuals' wealth. We test our model's predictions using U.S. data, and find that crime has a negative and significant impact on conspicuous consumption; also that this effect cannot be explained by the fact that some of these goods tend to be stolen by criminals. Finally, we show that this result is robust to different specifications and alternative measures of conspicuous consumption and crime.